Answer:
11 through 0
Step-by-step explanation:
Answer:
4/3
Step-by-step explanation:
This is a system of equations.
First, you set everything in terms of y.
Take the first equation and move set everything equal to y
y=0+2x
Since it’s 0, you don’t need to put it, so
y=2x works.
Then, you plug y=2x into the bottom equation, for the y.
-7x +3(2x)=2. You do this because now you have the same variable for both and it can be solved easily.
Then you can simplify.
-7x+3x = 2
Then combine like terms.
-4x = 2
Divide by -4 on each side.
x = -1/2
So, now that you have x, you can plug in your x-value back into the top equation.
-2(-1/2) + y = 0
Combine like terms
1+y=0
Get y by itself
y=-1
There you have it!
You can check by plugging in both values to any of the equations. We will use the top one here.
-2(-1/2) + (-1) =0
+1 + -1 = 0
It works!
So,
X= -1/2
Y= -1
Please rate me Brainliest answer :)
Answer:
Difference in the lengths of the polygons is (x + 7) units.
Step-by-step explanation:
Lengths of the given polygon = (7x + 2) units and (6x - 5) units
Therefore, difference in the given lengths = (7x + 2) - (6x - 5)
= (7x - 6x) + (2 + 5)
= x + 7
Therefore, difference in the lengths of the polygons is (x + 7) units.
Answer:
B
Step-by-step explanation:
29 + (-37) = 29 -37
Leave a like and mark brainliest if this helped